"Crippling and unfamiliar": Analysing the concept of perinatal anxiety; definition, recognition and implications for psychological care provision for women during pregnancy and early motherhood. Issue 23 (29th September 2020) - Folliard, Kelda J.; Crozier, Kenda; Wadnerkar Kamble, Meghana M.
Abstract: Aim: To clarify how perinatal anxiety is characterised within the current evidence base and discuss how a clearer definition and understanding of this condition may contribute to improving care provision by midwives and other healthcare professionals. Background: Perinatal anxiety is common, occurs more frequently than depression and carries significant morbidity for mother and infant. The concept of perinatal anxiety is ill‐defined; this can pose a barrier to understanding, identification and appropriate treatment of the condition. Design: Concept Analysis paper. Method: Rodgers' Evolutionary Model of Concept Analysis, with review based on PRISMA principles (see Supplementary File‐1). Findings: While somatic presentation of perinatal anxiety shares characteristics with general anxiety, anxiety is a unique condition within the context of the perinatal period. The precursors to perinatal anxiety are grounded in biopsychosocial factors and the sequelae can be significant for mother, foetus, newborn and older child. Due to the unique nature of perinatal anxiety, questions arise about presentation and diagnosis within the context of adjustment to motherhood, whether services meet women's needs and how midwives and other health professionals contribute to this. Most current evidence explores screening tools with little examination of the lived experience of perinatal anxiety. Conclusion: Examination of the lived experience of perinatal anxiety is needed to address the gap in evidence and further understand this condition. Service provision should account for the unique nature of the perinatal period and be adapted to meet women's psychological needs at this time, even in cases of mild or moderate distress.